2016
DOI: 10.18632/oncotarget.7482
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-323-3p inhibits cell invasion and metastasis in pancreatic ductal adenocarcinomaviadirect suppression of SMAD2 and SMAD3

Abstract: Pancreatic ductal adenocarcinoma (PDAC), which accounts for 96% of all pancreatic cancer cases, is characterized by rapid progression, invasion and metastasis. Transforming growth factor-beta (TGF-β) signaling is an essential pathway in metastatic progression and microRNAs (miRNA) play central roles in the regulation of various biological and pathologic processes including cancer metastasis. However, the molecular mechanisms involved in regulation of miRNAs and activation of TGF-β signaling in PDAC remain to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…Consistent with this model, suppression of miR-323a-3p augments and overexpression attenuates wound closure of a monolayer of cells (39). These findings imply that miR-323a-3p downregulation is necessary for the wound healing process.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with this model, suppression of miR-323a-3p augments and overexpression attenuates wound closure of a monolayer of cells (39). These findings imply that miR-323a-3p downregulation is necessary for the wound healing process.…”
Section: Discussionsupporting
confidence: 72%
“…SMADs can integrate multiple signaling pathways and regulate the expression of target genes in transforming growth factor‐β‐activated cells . In PC cells, SMAD2 overexpression could increase proliferation and invasion . Identification of the upstream regulators of SMAD2 will help elucidate its critical role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, luciferase reporter assays demonstrated that miR‐323‐3p directly regulated Smad2 in myoblast differentiation, and our research showed that overexpression of miR‐323‐3p restrained Smad2 expression. Interestingly, Smad2 was associated with miR‐323‐3p in another study . Besides, Smad2 is connected with the TGF‐β signal pathway, which regulates multiple cellular processes, such as cell proliferation and differentiation .…”
Section: Discussionmentioning
confidence: 92%